Formation of sowed mixtures of meadow grasses under the influence of mineral fertilizer - Т. І. МАRTSINKО; А. H. DZIUBAILO; N. V. KARASEVYCH (Передгірне та гірське землеробство і тваринництво)
The aim of the research was to identify the features of growth, development and formation of elements of productivity of perennial grasses in grass mixtures of hay morphotype depending on the level of mineral fertilizer.